Creative Writing Activities for Exploring Seventh Graders’ Written discourse Competence (2013)
AbstractThis project proposes Creative Writing as a pedagogical strategy to  improve 7th graders’ written discourse competence. Creative Writing is described as a chance to experiment freely with language, and it helpsto develop an efficient composing process in a meaningful environment. This paper describes a research project carried out at Técnico Comercial School in Jenesano Boyacá, with nine 7th graders as a sample. This was an action research study. Students’ writing, a final test, and a semi-structured final interview were used as data collection instruments. The findings from this study reveal students’ improvements through theuse of strategies to produce coherent and cohesive texts. Furthermore, the findings indicate students’ advancements in written production, characterized by the use of discourse elements throughout the body ofthe text.  Key words: creative writing, writing process, writings, writing skills, discourse competence.